HUBUNGAN ANTARA TINGKAT KECERDASAN EMOSIONAL DAN SIKAP SOSIAL TERHADAP KEDISPLINAN BELAJAR PESERTA DIDIK KELAS III SD N 01 KEBONDALEM - Lisa Anasari; Sunan Baedowi; Iin Purnamasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aim of this research is based on the fact that children are the nation's next generation who will grow and develop according to their age. By introducing emotions from an early age, children's emotions will develop and become one of the supporters of success in their future lives, accompanied by the formation of important social attitudes through good parenting in order to foster positive emotions and empathy in children. Because basically a low level of emotional intelligence will lead children to have negative social attitudes, such as having difficulty managing their emotions so they cannot solve the problems they face, being vindictive, always feeling right, being easily offended, easily getting emotional, and so on. The aim of this research is to determine the relationship between the level of emotional intelligence and social attitudes towards the learning discipline of class III students at SDN 01 Kebondalem. This type of research uses quantitative methods with a sample population of 15 respondents from class III students at SDN 01 Kebondalem. The sampling technique used was a non-random sampling technique with a purposive sampling method. The data analysis technique uses multiple linear regression with the classic assumption test, t test and F test. The results of this research show that there is a relationship between the variables between the level of emotional intelligence (X1), social attitudes (X2) and the learning discipline of class III students at SDN 01 Kebondalem (Y).